HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL LINE DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR SISWA - Puspita Dea Chantika; Turnomo Rahardjo (Interaksi Online, 2018)
The background of this study is the high number of social media users which are dominated by teenagers and the fact that learning achievement in Indonesia has not been optimal as evidenced by some research results. Learning is a process of interaction of educational communication which become one of the supporters of the nation's progress. This study aims to determine the relationship between The Intensity of Social Media LINE Usage (X1) with Student Learning Achievement (Y) and the relationship between Learning Motivation (X2) and Student Learning Achievement (Y). Theories which are used in this research are Displacement Effects Theory and Herzberg’s Two Factor Motivation Theory. This research type is an explanatory quantitative. Researcher uses non-probability sampling technique, with the number of samples of 145 respondents who are students of SMA N 1 Semarang. The results of this study indicate that the Intensity of Social Media LINE Usage (X1) proved to have a strong negative relationship with the Student Learning Achievement (Y). This relationship also can be seen from Kendall's Tau-b correlation test that shows the correlation coefficient of 0,530. The study findings show that students who have higher learning achievement scores tend to have lower levels of LINE usage intensity. The relationship between Student Learning Motivation (X2) with Student Learning Achievement (Y) shows a strong positive relationship. The study findings explain that students with high levels of learning motivation also have high learning achievement. This second hypothesis is acceptable because the correlation test results show the correlation coefficient of 0.601. The results of this study can be a reference for educational institutions and society, especially students that have to give more attention to factors related to student achievement, increase their learning motivation and not to use social media excessively.